2012
DOI: 10.1007/s10616-012-9504-8
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic effect of lipoic acid against mitomycin-C in human lymphocyte cultures

Abstract: Antitumor agents are used in therapy against many forms of human cancer. One of these is mitomycin-C (MMC). As with many agents, it can interact with biological molecules and can induce genetic hazards in non-tumor cells. One of the possible approaches to protect DNA from this damage is to supply antioxidants that can remove free radicals produced by antitumor agents. Lipoic acid (LA) is known as one of the most powerful antioxidants. The aim of this study was to investigate antigenotoxic effects of LA against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 95 publications
1
8
0
1
Order By: Relevance
“…In this study, we used this antitumor-antibiotic drug to test the possible antimutagenic activity of concrete and absolute oils. The study results of MMC in this experiment were coincided with previous reports (Fauth et al 2000;Yogesh and Fulzele 2009;Unal et al 2013). The group treated with MMC alone showed a significant elevation of chromosomal damage.…”
Section: Gc-ms Analysissupporting
confidence: 92%
“…In this study, we used this antitumor-antibiotic drug to test the possible antimutagenic activity of concrete and absolute oils. The study results of MMC in this experiment were coincided with previous reports (Fauth et al 2000;Yogesh and Fulzele 2009;Unal et al 2013). The group treated with MMC alone showed a significant elevation of chromosomal damage.…”
Section: Gc-ms Analysissupporting
confidence: 92%
“…It induces genotoxic and oxidative DNA damages, single/double DNA-strand breaks and apoptosis [31,32]. Chromosomal aberrations, sister chromatid exchanges and elevated micronucleus frequency in human lymphocytes were also reported [33]. Applying natural extracts enriched with antioxidants may facilitate the repair processes or neutralize the damaging factors that affect DNA molecules [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the antigenotoxic effects of Lipoic acid (LA) (Figure 1) against mitomycin-C induced chromosomal aberrations, sister chromatid exchanges, and micronucleus formation was observed in human peripheral lymphocytes. Moreover, LA exhibits both anticlastogenic and antimutagenic activity [6].…”
Section: Antimutagens With Antioxidant Potencymentioning
confidence: 99%